Some contribution to study on productive charecteristics of the palolo (Tylorrhynchus heterochaetus) Polychaeta - Nereidae in Hai Phong brackish water - Chuong, Nguyen Quang (Academia Journal of Biology, 2014)
The palolo (Tylorrhynchus heterochaetus, Quatrefages 1865) is a Polychaeta-Nereidae, living in muddy bottom of brackish water in estuaries coastal area. They are mainly captured during breeding. This type of the palolo Polychaeta is a favourite seafood, having highly nutrient value. Under large season. Demand for commercial food, together with overuse of pesticide for intensive agriculture and the destruction of the habitat, their population has over explored, leading to serious reduction of captured production. However, up to date, there is very little or almost no scientific information of the life cycle of this species. Knowledge in ecological characteristics such as tidal, weather change accompany with environmental parameters trigger induce spawning will help plan for conservation of the  palolo Polychaete in the future. This study result for the palolo was conducted in Hai Phong from 10/2007 to 6/2008. It has shown that breeding season is during two periods, May - June and October - November in accordance with full moon, critical to starting tidal and weather change (little raining, winter win….) Determination of environment during breeding times has indicated that temperature 26.57°C (water) and 26.070C (air), secchi disk at 29.5 cm, pH value 7.52, DO 5.79 mg/l and salinity 1.5‰ were the critical parameters for the spawning. Investigation of morphology has shown that Dtr = 166, Dk = 61; Ltr = 10.60 cm, Lk = 4.812 cm; Rtr = 2.31 mm, Rk = 5.64 mm; Ptr = 0.442 gr; Pk = 0.532 gr. Sex ratio determined through color and thereby found that during the time of spawning, the ratio between male and female was 1/1.9. Interestingly, unlike the previous thought that the Worm was more likely asexual. The result in this study strongly proved that it is sexually reproductive. Acknowledgment Many thanks is forwards to prof. Dr. Dang Ngoc Thanh, Institute of Science and Technology of Vietnam who has advise the study and give comments to all materials in the paper. Great thanks to prof. Dr. Thai Tran Bai for lab. Work, Ms. Phan Thi Van, Mr. Mai Van Tai and Mr. Vo Van Binh (CEDMA) for all study facilities. Field study has been supported from Mr. Tran Dinh Tuat in Tan Thang village, Chen Thang commune, An Lao district, who gave useful information contributing to the study.